KEKUASAAN NEGARA MENURUT UUD 1945 (ANALISA KEWENANGAN LEMBAGA NEGARA) - Sadjijono Sadjijono (Perspektif, 2005)
The division of power in the government system is an effort in cheking and balancing the interaction between agencies in the governance activity, and preventing power to be held by only one hand. Amandement of The Indonesian Constitution 1945 by Indonesia government is a step to represent the democrazy an constitution of the state, according to the constitusional system. The Amandement consists same changes to the Indonesian constitution, related to the check and balance of power. Firstly it has one agency which level is decreased from the highest agency into a high level agency.Secondly, the amandement has several agencies to experience a reduction and a boost up of power; More ever, a new agency is being establishedi as an impact of the amandement. Due to the alteration in the constitution system, the Parliament, at present, has very limited authority. It only responsible for composing amandement of the Constitution 1945, installing the President and Vice President, and also addressing empeachement. Ironically, with so few duties, its existence still absorb a big budget.